2022
DOI: 10.1111/ane.13653
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter imaging in progressive supranuclear palsy: Severe but nonspecific to subtypes

Abstract: Background Previous studies with a limited sample size suggested more severe dopaminergic transporter (DAT) lesions in the striatum of progressive supranuclear palsy (PSP) than those in Parkinson's disease (PD) and multiple system atrophy–parkinsonism (MSA‐P). However, few studies had taken various subtypes of PSP into consideration, making the reanalysis of DAT imaging in larger PSP cohort with various subtypes in need. Objectives To compare the dopaminergic lesion patterns of PSP with MSA‐P and PD, and to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Severe dopaminergic lesions in the striatum were common in PSP, as shown in the DAT PET imaging ( Yoo et al, 2018 ; Chen et al, 2022 ). For the first time, we reported the striatal dopaminergic dysfunctions in caudate and anterior putamen contributed to the disease severity in PSP, but not in posterior putamen.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Severe dopaminergic lesions in the striatum were common in PSP, as shown in the DAT PET imaging ( Yoo et al, 2018 ; Chen et al, 2022 ). For the first time, we reported the striatal dopaminergic dysfunctions in caudate and anterior putamen contributed to the disease severity in PSP, but not in posterior putamen.…”
Section: Discussionmentioning
confidence: 91%
“…For the first time, we reported the striatal dopaminergic dysfunctions in caudate and anterior putamen contributed to the disease severity in PSP, but not in posterior putamen. We previously reported that the lesions in posterior putamen were more prominent than caudate in PSP, reflecting specific degenerative patterns in Parkinsonism ( Chen et al, 2022 ). Pathologically, dopaminergic projections to the striatum were from different parts of substantial nigra, with putamen from ventral part and caudate from dorsal part ( Fearnley and Lees, 1991 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the Southampton method, which we used in this study for the analysis of the striatal DAT binding, does not allow the analysis by separation of striatal subregions. It has been reported that the striatal DAT binding is lower in patients with PSP than in those with PD or MSA-P, especially in the caudate (Chen et al 2022 ; Kaasinen et al 2019 ). Future studies should consider evaluating the striatal DAT binding of each subregion separately and comparing the differences among each diagnosis.…”
Section: Discussionmentioning
confidence: 99%